Microbial profiling of community-acquired pneumonia in patients with and without chronic obstructive pulmonary disease: a comprehensive molecular diagnostics study - Dagfinn Lunde Markussen; Christoffer Lindemann; Sondre Serigstad; Synne Jenum; Christian Ritz; Harleen M. S. Grewal (Pneumonia)
Abstract Background Community-acquired pneumonia (CAP) causes substantial morbidity and mortality, particularly in patients with chronic obstructive pulmonary disease (COPD). This study compares the microbial detections in CAP patients with and without COPD using culture based and molecular diagnostic methods. Methods This prospective study included 412 hospitalized pneumonia patients (136 with COPD). Lower respiratory tract samples were analysed with traditional cultures and a multiplex PCR panel (FilmArray Pneumonia Panel Plus). Multivariable Poisson regression identified predictors of Pseudomonas aeruginosa detection, and logistic regression estimated detection probability using the top predictors. Results Overall pathogen detection rates were similar between groups, but P. aeruginosa was significantly more common in COPD patients (12.5% vs. 3.1%; p < 0.001). In adjusted analyses, each additional year of age increased the risk of P. aeruginosa by 5% (RR 1.05; 95% CI 1.01–1.09), while advanced COPD (GOLD 3–4) conferred a four‐fold higher risk (RR 4.29; 95% CI 1.94–9.46), diabetes mellitus a four‐fold risk (RR 4.04; 95% CI 1.97–8.29), and prior P. aeruginosa detection a five‐fold risk (RR 5.03; 95% CI 2.44–10.36). Inhaler use, bronchiectasis, and recent hospitalization were not independently associated. Conclusion Although overall microbial detection rates were comparable between groups, P. aeruginosa was disproportionately prevalent in high-risk COPD individuals. While most COPD patients with pneumonia can be managed with standard empirical antibiotics, empirical coverage for P. aeruginosa should be considered for selected high-risk patients. Prospective studies are warranted to evaluate targeted P. aeruginosa coverage to optimize antibiotic stewardship and improve outcomes. Graphical Abstract